Provision of recreational facilities by Local Government in South Africa : a case of City of Tshwane - Modisane, N. M.; Diale, A. J.; Moeti, K. B. (International Conference on Public Administration and Development Alternative (IPADA), 2019)
The provision of recreational facilities in South Africa has been receiving considerable attention as a significant part of the character of a planned community. This is due to their value in contributing to the on-going economic vitality of communities throughout the country in areas of tourism, revenue producers for entrepreneurs and recreational spaces within natural resources. This realization has placed a mammoth task on authorities within the local sphere of government. Municipalities are at the epicenter of the both the provision of these facilities in terms of availability of resources, quality and accessibility of these facilities by local communities. To ensure that these facilities contribute to the strategic value and a direction of sustainable recreational services, this article presents the results of a study conducted within Tshwane Metropolitan Municipal area in predominantly / underdeveloped communities. A case study design research paradigm was designed for this study in which data was collected through survey questionnaires, official reports and archival documents. What the study revealed is the incongruence of the officials' views as against the communities' expectations. The recommendations are presented to effect alignment of this challenge. Keywords: Benefit-based management, Metropolitan municipality, Recreation facilities, Tshwane metropolitan municipal
The 4th Annual International Conference on Public Administration and Development Alternatives 03 - 05 July 2019, Southern Sun Hotel, OR Tambo International Airport, Johannesburg, South Africa
Keywords: Benefit-based management; Metropolitan municipality; Recreation facilities; Tshwane metropolitan municipal; Tshwane (Municipal Government)